A Study of the Methods of Teaching Islamic Theology Courses in Farhangiyān University from the View of Student Teachers - Katayoon Hamidizade (پژوهش در آموزش معارف و تربیت اسلامی)
The purpose of the present research is to study viewpoints of student teachers about methods of teaching theology courses at Farhangiyān university. The research method is quantitative survey and the statistical population consists of 1711 students at Frahangiyān university in Arak among whom 313 members were chosen by multistage stratified sampling. For data collection, Halimi Jelodār Questionnaire (2015) was used. The results show that 83% of student teachers assume that using modern methods is necessary for teaching Islamic theology. Besides, they are interested in the adaptation of Islamic theology courses and teaching them based on their own specialized majors. 27.7% of students consider the quality of Islamic theology textbooks as average and evaluate the performance of their professors to be 46%. Student teachers demand profound and practical education of the above courses and emphasize on some elements such as analysis as well as criticism of subjects for the improvement of students.